(untitled) (INNOVATIVE ECONOMY, 2020)
Lypynska O.A., Poznanska I.V. PRIORITY MEASURES FOR PROVIDING THE DEVELOPMENT OF INTERMODAL AND MULTIMODAL TRANSPORTATION Purpose. The aim of the article is the development of methodological provisions for elimination of problems of development of intermodal and multimodal transportations in Ukraine. Methodology of research. The methodological basis of the study is a dialectic method of cognition and a systematic approach to the study of economic processes in the implementation of multimodal and intermodal transport. The method of analysis and synthesis is used in the study of the main international and national regulatory legal acts regarding the functioning of safe supply chains. The method of induction and deduction is used in the formulation of generalizations, theoretical conclusions on the basis of the studied material. Findings. The main shortcomings are identified and recommendations on implementation of the mechanism of functioning of authorized economic operators in Ukraine are provided. As a result of the analysis of international and national practices in the formation of economic relations in the implementation of mixed transport in Ukraine and in the world, the latest trends of changes in requirements for the improvement, simplification and updating of customs legislation of the EU and the USA have been determined. It is determined that the last measures for optimization of multimodal and intermodal transport, both at the international and national levels, are aimed at ensuring the security of the supply chain. It is substantiated that the principle of mutual recognition is fundamental in the work of the UEA Institute for the elimination of obstacles to the free movement of goods within the territory of Ukraine. Originality. The principles to be followed in forming the mechanism of functioning of the UE in Ukraine are ascertained: expediency; mutual recognition; openness (availability of information); compliance with legal norms; security of the supply chain. Practical value. Creation of conditions for the functioning of the UE system in Ukraine will increase the competitiveness of Ukrainian water transport enterprises at the international level, with the participation of domestic enterprises in the formation of a safe supply chain. The results of the study can be proposed for implementation in the formation of separate components of the customs policy of Ukraine. Key words: multimodal and intermodal transportation; water transport; authorized economic operator; safe supply chains.